Fuel consumption and consumption optimization - Hilgers, Michael; Achenbach, Wilfried 1955- (Springer Vieweg, 2021)
The aim of this work, consisting of 9 individual, self-contained booklets, is to describe commercial vehicle technology in a way that is clear, concise and illustrative. Compact and easy to understand, it provides an overview of the technology that goes into modern commercial vehicles. Starting from the customer's fundamental requirements, the characteristics and systems that define the design of the vehicles are presented knowledgeably in a series of articles, each of which can be read and studied on their own. In this volume, Fuel Consumption and Consumption Optimization, the main focus is placed on the factors for optimizing consumption in the conventional vehicle. Fuel consumption can be optimized by four different factors: the technology of the vehicle, the conditions of its operation, the behavior of the driver and the maintenance and upkeep of the vehicle. These aspects are described in a way that is easily understood for training and practical application. Content Fuel consumption and consumption optimization on conventional trucks.- Motion resistance and energy loss.- Vehicle technology.- Operating conditions of the vehicle.- The influence of the driver on fuel consumtion.- Maintenance of the vehicle and service fluids.- Concluding remarks on the topic of consumption.- Comprehension questions.- Abbreviations and symbols. The target groups Participants in master classes and those studying individual aspects of commercial vehicle technology Professors and lecturers instructing in the field of commercial vehicle technology Consultants and experts who need background knowledge and technical expertise regarding commercial vehicle technology Personnel working in the commercial vehicle technology or supply industry who are assigned to a new work area Cost planners and logistics companies The Authors Dr. Michael Hilgers is currently director of the testing center at BFDA, a Foton Daimler truck joint venture in China. Before that he was head of different development departments in Commercial Vehicle Development at Mercedes-Benz Trucks. Dr. Wilfried Achenbach has worked in the automotive industry for over 30 years. Recently he retired as Head of Development at Daimler Trucks North America.